Bibliographic Indexes on Trade, Merchants, and Entrepreneurship in Siberia in the Second Half of the XIX – Early XX Centuries: a Historiographic Review - O. G. Klimova (Kemerovo State University, 2021)
The research traced the evolution of bibliographic indexes on trade, merchants, and entrepreneurship in Siberia in the second half of the XIX – early XX centuries. Bibliographic indexes are publications of a special type that carry valuable information, which makes them an integral part of Siberian studies. This material expands the existing ideas about the nature of the development of trade and economic activities of business people in Siberia. Bibliographic indexes are still popular as a convenient way of obtaining necessary information. Bibliographies of the pre-revolutionary, Soviet, and post-Soviet periods have their own distinct features. The indexes under discussion coincided with the main stages of economic and social life in Siberia. They proved to be an important part of the history and culture of  Siberia. The number of published bibliographic products gradually increased, the publication process involved institutions, societies, researchers, and bibliographic movement. Indexes contributed to the development of historical science. Bibliographic thematic reflected the historical process. However, the historiography of the present issue needs further research and deserves a monograph.